The Multicultural Islamic Education at Muhammadiyah University of Mataram - Palahuddin Palahuddin; Mappanyompa Mappanyompa (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2022)
This study aimed to determine the responses of non-Muslim students to AIK (Al-Islam and Kemuhammadiyahan) learning materials and the factors behind their responses to AIK learning. This quantitative field research applied a case study model where the respondents and the sample in this study were non-Muslim students at the Faculty of Social and Political Sciences (Fisipol) University of Muhammadiyah Mataram (UMMAT), which were taken through a systemic purposive sampling. After that, the data collection was carried out using closed and mixed questionnaires. Then all data were analyzed using percentile descriptive statistical analysis techniques and drawn to a conclusion using deduction and induction methods. The results of this study were first: the response of non-Muslim students to Al-Islam and Kemuhammadiyahan (AIK) learning materials was very positive by attending all meetings held by AIK lecturers, both online and offline meetings. This is evidenced by the data processing results showing that the majority of students stated that they were satisfied as much as 62%, while 8% said they were very satisfied, and as many as 30% said they were quite satisfied. Second, the factors behind the response of non-Muslim students to AIK learning are: 1) campus policies that require all students, both Muslim and non-Muslim, to take AIK courses, 2) awareness that arises in students to know Islam more even though in the end it did not become their belief, 3), the desire to realize the nature of religious tolerance in fellow students on the UMMAT campus.